Design of TMD with nonlinear viscous fluid dampers with varying damping for 6-Storey building with two different structural damping - Raju, K. Rama; Deepthi, M.; Narayanan, R.R. Aathish; Desai, V. Bhaskar (Journal of Structural Engineering, 2024)
Dampers have become more popular for vibration control of structures, because of their safe, effective and economical design. Tuned mass damper (TMD) is the most popular passive type of control system especially for buildings subjected to earthquake/ high winds. The properties of the TMD required for optimum performance depends on stiffness, mass and damping distribution of the structure/building or their components need to be isolated from vibrations. From experimental results, the optimum parameters such as optimum tuning ratio (f) and optimum damping ratios (ξd) for TMD were derived by two types of analytical formulations. A 6-Storey steel framed building with TMD is modeled in 3D using SAP2000. The 6-Storey building model is reduced to 6 DOF system and optimum parameters of TMD are computed using the methods by two types of formulations. Two analytical formulation are found to give same optimum tuning ratio, but optimum effective damping ratio are found to be differing. With the optimum tuning ratio and the parameters of TMD obtained by the two methods, the damping in TMD is varied using nonlinear viscous fluid dampers (NVFD) for finding the responses of building in X-direction subjected to one near field earthquake excitation (El Centro with PGA of 4.417 m/s²) and two far field earthquake excitations (Northridge, Kobe with PGA of 8.2676 and 8.1782 m/s² respectively) with their PGA normalized to 0.35g. The effectiveness of the TMD in reducing the responses of structures for two different structural damping of 2% and 5% by increasing effective damping of NVFD in TMD from 0.05 to 0.25 is found.